Parenting style: a case study among students in SMK Seremban 3 / Siti Hajar Noh, Ummi Atifah Mohd Norsah and Nur Aishah Zaharah Mohmad Sujana - Noh, Siti Hajar; Mohd Norsah, Ummi Atifah; Mohmad Sujana, Nur Aishah Zaharah (Faculty of Computer And Mathematical Sciences, 2017)
Parenting plays an important role in the child development. This study is aimed at identifying the relationship between demographic profile, parents' parenting styles and also the significant factor based on parenting styles. The respondents were 50 male and 50 female students between the ages of 13 to 15 from secondary school in Seremban 3. They were administered the Alabama Parenting Questionnaire by using stratified random sampling to evaluate their parents' parenting style; Authoritative, Authoritarian and Permissive. The data was analysed with IBM SPSS Statistics 21.0 version. This study used descriptive analysis, chi-square test of independence and multinomial logistic regression in order to achieve research objectives. Results indicated that almost parents of lower form student in SMK Seremban 3 practicing an Authoritative parenting style. Keywords: parenting styles; Authoritative, Authoritarian, Permissive